AHMET CEVDET PASHA'S HISTORIOGRAPHY AND HIS OPINIONS ON HISTORY EDUCATION AND HISTORY TEACHING - Sezai ÖZTAŞ (International Journal of Eurasia Social Sciences, 2017)
Ahmet Cevdet Pasha, who had been in important positions in the Ottoman Empire in the 19th century, is a historian, jurist, educator, linguist and poet as well as a statesman. There are very few people in Ottoman history who carry all of these features together. In this respect, many researches have been done about Ahmet Cevdet Pasha up to the present day. Studies carried out in different fields with each passing day about him, are showing that these investigations are not yet completed. Ahmet Cevdet Pasha, who carries on many features, is one of the most important chronicler and historian of the Ottoman Empire in 19th century. Due to a great number of Ottoman historians are state chronicler, they usually deal with events in chronological order. Ahmet Cevdet Pasha is one of the few Ottoman historians who can go beyond this, use his own opinions about the causes and consequences of the events and take criticism as a method while deciding upon the sources. Ahmet Cevdet Pasha's studies and publishings in various fields affected histitles as historiographer and history educator positively. Having a multidisciplinary approach, Ahmet Cevdet Pasha brought a new understanding to Ottoman historiography and was in the struggle to deliver a philosophy of history and methodology. In this study, Ahmet Cevdet Pasha's historiography and his opinions on history education and history teaching will be discussed.